Supply Chain Ontology: Model Overview and Synthesis - Moh. Muklis Sulaeman; Mugi Harsono (Jurnal Mantik, 2021)
Supply chain ontology as an important medium for solving information system interoperability problems. To inform future supply chain ontology research, this paper sets out to review and analyze existing supply chain ontology models. An extensive literature review was conducted which identified six supply chain ontology models together with the three criteria that form the framework for comparison. After applying a framework has been identified which should provide insight into potential future research. The general conclusion is that we are far from using ontologies to solve information system interoperability problems. Our analysis has shown that too much emphasis is placed on the organization and structure of human knowledge of supply chains than on understanding supply chain realities. Seen from a 'philosophy of science' perspective, all the models reviewed have ontological flaws. More rigorous and theoretical analysis is needed if a more realistic and robust supply chain system is to be developed.